2022
DOI: 10.1093/bib/bbac256
|View full text |Cite
|
Sign up to set email alerts
|

Portable sequencing of Mycobacterium tuberculosis for clinical and epidemiological applications

Abstract: With >1 million associated deaths in 2020, human tuberculosis (TB) caused by the bacteria Mycobacterium tuberculosis remains one of the deadliest infectious diseases. A plethora of genomic tools and bioinformatics pipelines have become available in recent years to assist the whole genome sequencing of M. tuberculosis. The Oxford Nanopore Technologies (ONT) portable sequencer is a promising platform for cost-effective application in clinics, including personalizing treatment through detection of drug res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…In a recent study, Marin et al (2022) found several pe / ppe genes with good mappability and variant detection with short-read sequencing platforms that could be included in WGS analysis with confidence. The majority of these genes belonged to class C in our analysis, congruent with a better coverage of the conserved pe / ppe genes found also in previous studies ( Gómez-González et al, 2022 ), while class K genes were found with lower scores for Illumina mappability. Long read sequencing technologies can be of use to overcome this problem ( Gómez-González et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a recent study, Marin et al (2022) found several pe / ppe genes with good mappability and variant detection with short-read sequencing platforms that could be included in WGS analysis with confidence. The majority of these genes belonged to class C in our analysis, congruent with a better coverage of the conserved pe / ppe genes found also in previous studies ( Gómez-González et al, 2022 ), while class K genes were found with lower scores for Illumina mappability. Long read sequencing technologies can be of use to overcome this problem ( Gómez-González et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…The majority of these genes belonged to class C in our analysis, congruent with a better coverage of the conserved pe / ppe genes found also in previous studies ( Gómez-González et al, 2022 ), while class K genes were found with lower scores for Illumina mappability. Long read sequencing technologies can be of use to overcome this problem ( Gómez-González et al, 2022 ). We analyzed PacBio assemblies to provide the most comprehensive picture to date of genetic diversity in all 169 pe / ppe genes.…”
Section: Discussionsupporting
confidence: 92%
“…The introduction of the LRS technology represents a valid alternative to the SRS approaches, because it allowed a better characterization of the MTB genome, e.g., InDel and repetitive regions. Comparing the results between SRS and LRS, different studies highlight genome regions where the SRS lacks accuracy due to limit of the technology ( Modlin et al, 2021 ; Peker et al, 2021 ; Gómez-González et al, 2022 ; Marin et al, 2022 ). Although LRS approaches still present a high-error rate (~5–15%), their random nature allows to improve accuracy with higher coverage ( Rhoads and Au, 2015 ; Athanasopoulou et al, 2021 ; Amoutzias et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each human readset was randomly downsampled to 1 Gbp using rasusa (v0.7.1) [ 51 ]. For the M. tuberculosis component, we used Illumina HiSeq 4000 (accession: ERR245682) and Nanopore R10.3 (accession: ERR8170871) [ 52 ] (we used R10.3 as there were no R10.4 M. tuberculosis WGS datasets publicly available). For the bacterial component, we used Illumina MiSeq (accession: ERR7255689) and Nanopore R10.4 (accession: ERR7287988) reads from the ZymoBIOMICS HMW DNA Standard D6322 (Zymo Research), which contains 7 bacterial and 1 fungal strain(s) [ 53 ]—none of which are Mycobacterium .…”
Section: Methodsmentioning
confidence: 99%